What Are Structural Reforms?. Issue 1 (June 2013) - Macaes, Bruno
Policymakers are faced with a crucial choice between ameliorating the symptoms of existing economic problems and trying to address the causes of these problems. The latter goal is what explains the emergence and growing popularity of a relatively new idea: structural reform. What are structural reforms and what challenges do they face? We must start by understanding what the idea implies. First, it calls for a new approach, a general vision of the economy as an integrated system, where policy complementarities abound. Second, it expresses a certain understanding of the relationship between state and market, whereby the state has a foundational or institutional role but does not interfere with economic activity and economic agents. Third, structural reform is in many respects at odds with elements of our political systems, which face increasing challenges when fundamental economic change becomes necessary.